EMERGING TRENDS IN THE DEVELOPMENT OF LOCAL WISDOM-ORIENTED TEACHING MATERIALS FOR CHARACTER EDUCATION IN ELEMENTARY SCHOOLS: A SYSTEMATIC REVIEW (2015–2025) - M Agung Alwanda; Mintarsih Arbarini; Bambang Subali; Ellinawati Ellinawati (Jurnal Cakrawala Pendas, 2026)
The advancement of education in the digital era requires learning innovations that not only focus on cognitive development but are also rooted in cultural and moral values. Integrating local wisdom into instructional materials serves as a strategic effort to strengthen students’ character while preserving national cultural identity. This study aims to map research trends, analyze the contribution of local wisdom-based instructional materials to character education, and identify research gaps within studies published from 2015 to 2025. The research employed a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework and supported by bibliometric analysis using VOSviewer. Data were obtained from 991 articles indexed in Google Scholar and Scopus, from which 29 met the inclusion criteria for further analysis. The findings reveal a significant increase in research publications over the past decade with two main orientations: the integration of cultural values to strengthen character education and the development of innovative learning media. The media developed include educational comics, storybooks, pop-up books, e-modules, and interactive multimedia designed to cultivate responsibility, religiosity, cooperation, and appreciation for local culture. However, limitations remain in the diversity of cultural contexts, long-term effectiveness testing, and the digitalization of learning media, Overall, local wisdom-based instructional materials play a crucial role not only in cultural preservation but also in holistic character development. Future studies should strengthen digital integration, broaden cross-cultural applications, and conduct longitudinal evaluations to support the implementation of the Merdeka Curriculum and the Profil Pelajar Pancasila.